1995
DOI: 10.1002/rcm.1290091510
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase reactivity of protonated cyclodepsipeptidic toxins: The study of a systematic fragmentation pathway under fast‐atom bombardment desorption

Abstract: A systematic pathway of fragmentation for several protonated cyclohexadepsipeptides is demonstrated by positive-ion fast-atom bombardment linked-scan mass spectrometry. It involves classical sequential acylium and immonium ions, but also, unusual fragment ions characteristic of this family of compounds.Since fast-atom bombardment (FAB) and liquid secondary ion mass spectrometry (LSIMS) ionization techniques have been introduced, structural analyses of linear and cyclic peptides have improved. 1 . 2 3 3 Thus, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…30 ; the superscript deÐnes the pair of amino acids between which the primary splitting takes place).31 In addition to these series, internal a destruxin-speciÐc fragment ion denoted D`was detected. 29 The ion composition of the in-source CID APCI mass spectra is qualitatively consistent with that observed in the high-energy CID spectra of [M ] H]ì ons generated by FAB ionization. 29 The reasonable abundance of sequence ions seems to be a strong advantage of the APCI mass spectra.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…30 ; the superscript deÐnes the pair of amino acids between which the primary splitting takes place).31 In addition to these series, internal a destruxin-speciÐc fragment ion denoted D`was detected. 29 The ion composition of the in-source CID APCI mass spectra is qualitatively consistent with that observed in the high-energy CID spectra of [M ] H]ì ons generated by FAB ionization. 29 The reasonable abundance of sequence ions seems to be a strong advantage of the APCI mass spectra.…”
Section: Resultssupporting
confidence: 72%
“…29 The ion composition of the in-source CID APCI mass spectra is qualitatively consistent with that observed in the high-energy CID spectra of [M ] H]ì ons generated by FAB ionization. 29 The reasonable abundance of sequence ions seems to be a strong advantage of the APCI mass spectra. The presence of corresponding immonium ions provides information on the amino acid composition of a given destruxin (Fig.…”
Section: Resultssupporting
confidence: 72%
“…The behavior of cyclopeptides 2,[5][6][7][8][9][10][11]17,18 and cyclodepsipeptides [19][20][21][22][23][24][25][26]28 in FAB-MS has been described in the literature and the following features were reported. The initial protonation occurs preferentially on a basic site and in particular on a tertiary amide when present.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing destruxins or sequencing synthetic cyclohexapeptides have been demonstrated as real challenges either using lowenergy collision-induced dissociation (CID) in a QQQ instrument3 or using high-energy CID in an EB instrument . 4 Nevertheless, using first-generation product-ion spectra of these cyclic peptides, it has been observed that only sequential ions of Bi or Ai types are observed with low-energy CID, while, using highenergy CID, Bi and Ai ions are accompanied by internal fragment ions. Both analyses required numerous first-generation product-ion spectra from many precursors.…”
mentioning
confidence: 98%